Association of Obesity, Sarcopenia, and Sarcopenic Obesity With Hypertension in Adults: A Cross-Sectional Study From Ravansar, Iran During 2014–2017 - Pasdar, Yahya; Darbandi, Mitra; Rezaeian, Shahab; Najafi, Farid; Hamzeh, Behrooz; Bagheri, Amir (Frontiers in Public Health, 2022)
Background and aims: Hypertension may lead to disability and death by increasing the risk of cardiovascular disease, kidney failure, and dementia. This study aimed to determine the association between obesity, sarcopenia and sarcopenic obesity, and hypertension in adults resident in Ravansar, a city in the west of Iran. Methods: This cross-sectional study was conducted on 4021 subjects from baseline data of Ravansar Non-Communicable Disease (RaNCD) cohort study, in the west region of Iran, from October 2014 up to February 2017. Body composition was categorized based on measurements of muscle strength, skeletal muscle mass and waist circumference, to the obese, sarcopenia, sarcopenic obese, and normal. Univariate and multiple logistic regression models were used to examine the relationships, using the STATA 15 software. Results: The mean age of the participant was 47.9 years (SD: 8.4), BMI was 26.84 kg/m2 (SD: 4.44) and the prevalence of hypertension was 15.12 percent. The prevalence of obesity, sarcopenia, and sarcopenic obesity were 24.37%, 22.01%, and 6.91%, respectively. Body composition groups had significant differences in age, total calorie intake, BMI, skeletal muscle mass, and muscle strength (P-value ≤ 0.001). In crude model, the obese (OR= 2.64; 95% CI: 2.11-3.30), sarcopenic (OR= 2.45; 95% CI: 1.94-3.08) and sarcopenic obese (OR= 3.83; 95% CI: 2.81-5.22) groups had a higher odds of hypertension. However, in adjusted models, only the obese group had a higher likelihood of hypertension (OR= 2.18; 95% CI: 1.70-2.80). Conclusion: This study showed that obesity was associated with hypertension, whereas sarcopenia and sarcopenic obesity had no significant relationship with hypertension.